2021
DOI: 10.3233/apc210185
|View full text |Cite
|
Sign up to set email alerts
|

IoT Based Security Alerts for the Safety of Industrial Area

Abstract: The security of any business plays a vital role. All enterprises expect high security because of the increase in robbery. It is challenging to manage security with traditional ways of protection. This paper emphasizes the sensor-based security system to protect against any unwanted entry in the business area. This system is developed using IoT-based sensors, and electronic materials develop the security system. The present scenario ensures protection and security have become inevitably necessary. There is regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…(11,12) A method for encephalon tumor segmentation was suggested based on a hybrid type of approach using FCM, and they reached 90 % noise level precision. (13) When compared to first-order statistical characteristics, (14) it was found that using a wavelet transform and SVM's technique resulted in better prognoses and enhanced clinical factors such as tumor volume, and tumor stage. (15) Using PCA and SVMs, a 94 % relegation accuracy (SVM) was Salud, Ciencia y Tecnología.…”
Section: Related Workmentioning
confidence: 99%
“…(11,12) A method for encephalon tumor segmentation was suggested based on a hybrid type of approach using FCM, and they reached 90 % noise level precision. (13) When compared to first-order statistical characteristics, (14) it was found that using a wavelet transform and SVM's technique resulted in better prognoses and enhanced clinical factors such as tumor volume, and tumor stage. (15) Using PCA and SVMs, a 94 % relegation accuracy (SVM) was Salud, Ciencia y Tecnología.…”
Section: Related Workmentioning
confidence: 99%